2012
DOI: 10.1093/ejcts/ezs572
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved human allografts (homografts) for the management of graft infections in the ascending aortic position extending to the arch

Abstract: Surgery for infected Dacron grafts in the ascending aortic position with involvement of the arch can be performed with an acceptable perioperative mortality. In case of degeneration of the valve, reoperations can be performed with good results in experienced hands. Therefore, we consider the concept of complete explantation of all infected material and replacement with homografts a successful treatment strategy. Nevertheless, close follow-up of the patients is mandatory so as not to miss any degeneration or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
16
0
4
Order By: Relevance
“…However, surgical mortality and morbidity are still a major concern with traditional replacement due to the invasiveness and complexity of the procedure, emergency conditions, contaminated field, and the difficulties of exposure in the redo aortic setting (Czerny et al 2011). Two recent explants studies from dedicated aortic centers, to our knowledge the largest published series, have reported a hospital mortality which ranges from 24% to 27% (Coselli et al 1999; Khaladj et al 2013). These have been reports of small series, including 11 patients from Texas and 17 patients from Hanover in which redo ascending aortic replacement and/or aortic arch replacement were performed by using Dacron grafts or homografts without recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgical mortality and morbidity are still a major concern with traditional replacement due to the invasiveness and complexity of the procedure, emergency conditions, contaminated field, and the difficulties of exposure in the redo aortic setting (Czerny et al 2011). Two recent explants studies from dedicated aortic centers, to our knowledge the largest published series, have reported a hospital mortality which ranges from 24% to 27% (Coselli et al 1999; Khaladj et al 2013). These have been reports of small series, including 11 patients from Texas and 17 patients from Hanover in which redo ascending aortic replacement and/or aortic arch replacement were performed by using Dacron grafts or homografts without recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…These have been reports of small series, including 11 patients from Texas and 17 patients from Hanover in which redo ascending aortic replacement and/or aortic arch replacement were performed by using Dacron grafts or homografts without recurrences. The leading cause of mortality was multiple organ failure following sepsis or profound bleeding (Coselli et al 1999; Khaladj et al 2013). Successful redo in-situ replacement surgery in this series was even among early survivors associated with severe postoperative complications such as wound infection, respiratory failure, stroke, and multiple organ failure (Coselli et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Хирургическое лечение в свою очередь может быть одноэтапным и многоэтапным. К нему относятся открытое ведение раны, применение вакуумных повязок, средостенных проточно-промывных систем, пластика средостения с укрытием протеза васкуляризованными аутотканями (лоскут из большого сальника, мышечный лоскут), а также репротезирование инфицированного протеза биологическими протезами [5][6][7].…”
Section: кардиология и сердечно-сосудистая хирургия 4 2018unclassified
“…Существуют общие рекомендации по хирургическому лечению ИПА -это удаление инфицированных и некротизированных тканей средостения, хирургическая обработка, удаление инфицированного протеза с последующим репротезированием аорты [4,9]. Однако эти операции сложны и тяжело переносятся пациентами [7], сохраняются высокие цифры госпитальной летальности (до 42%) [4]. В связи с этим распространенными являются протез-сохраняющие методы хирургического лечения, к которым относится пластика средостения васкуляризованными аутотканями, такими как большой сальник, мышечный лоскут из большой грудной мышцы [3,5,8].…”
Section: кардиология и сердечно-сосудистая хирургия 4 2018unclassified
“…Because, according to my opinion, there is great difference of operative techniques in the most common type so arterial occlusive diseases seen in Bangladesh [4,8,10]. In case of obliterative endarteritis only Endarterectomy have good prognosis [4,8] while, in case of atherosclerotic occlusive disease angioplasty with stenting or placemat of arterial graft gives better result [10][11][12][13][14][15][16][17][18][19][20][21]. It is observed that, good long time patency /placement of arterial grafts in atherosclerotic occlusive diseases of male population in more than 50 years of age.…”
Section: Introductionmentioning
confidence: 99%